Siderite micro-modification for enhanced corrosion protection. (December 2017) - Taleb, Wassim; Pessu, Frederick; Wang, Chun; Charpentier, Thibaut; Barker, Richard; Neville, Anne
Abstract Production of oil and gas results in the creation of carbon dioxide (CO2 ) which when wet is extremely corrosive owing to the speciation of carbonic acid. Severe production losses and safety incidents occur when carbon steel (CS) is used as a pipeline material if corrosion is not properly managed. Currently corrosion inhibitor (CI) chemicals are used to ensure that the material degradation rates are properly controlled; this imposes operational constraints, costs of deployment and environmental issues. In specific conditions, a naturally growing corrosion product known as siderite or iron carbonate (FeCO3 ) precipitates onto the internal pipe wall providing protection from electrochemical degradation. Many parameters influence the thermodynamics of FeCO3 precipitation which is generally favoured at high values of temperatures, pressure and pH. In this paper, a new approach for corrosion management is presented; micro-modifying the corrosion product. This novel mitigation approach relies on enhancing the crystallisation of FeCO3 and improving its density, protectiveness and mechanical properties. The addition of a silicon-rich nanofiller is shown to augment the growth of FeCO3 at lower pH and temperature without affecting the bulk pH. The hybrid FeCO3 exhibits superior general and localised corrosion properties. The findings herein indicate that it is possible to locally alter the environment in the vicinity of the corroding steel in order to grow a dense and therefore protective FeCO3 film via the incorporation of hybrid organic-inorganic silsesquioxane moieties. The durability and mechanical integrity of the film is also significantly improved. Fuel pipelines: using corrosion to our advantage Engineering the FeCO3 films that form in gas and oil pipelines offers a cheap and environmentally friendly option for corrosion management. Thousands of kilometres of steel−based fuel transportation networks across the US and the UK require protection from wet and corrosive CO2, and current methods involve the expensive and environmentally-harmful deployment of corrosion inhibitor chemicals. A team led by Wassim Taleb at the University of Leeds in the UK show that adding a silicon-rich filler into the mix not only accelerates growth of the protective FeCO3 corrosion product on the internal pipe walls, but also enhances the strength and durability of these films, slowing the rate of further steel degradation. Being able to modify these films in a batch treatment could drastically change the way that corrosion is managed in fuel pipelines.